Analisis Perhitungan Dan Pengukuran Sistem Suplay Ac/Dc Untuk Kontrol Beban Di Gardu Induk Pekalongan - Meriani meriani; Anton Savalas; Mekar Ria Pangaribuan (UNIVERSITAS PROF. DR. HAZAIRIN, SH BENGKULU, 2021)
Abstract This abstract was conducted because of the lack of attention and maintenance carried out on the AC / DC supply, which is actually very important at the substation. How to make an AC/ DC supply system at Pekalongan substation fast work with high reliability and what steps are taken to reduce the impact of disruption or damage to equipment at the Pekalongan substation especially AC/ DC supply for load control. The research objective was to 1) analyze the AC/ DCs supply system at the Pekalongan substation, 2) Know the intermediate error value the measurement results on the Supply AC/ DC system are measured by the calculated value. The method used in this analysis consists of several stages, namely: 1) planning, 2) start, 3) Action, 4) Observation, 5) Reflection, 6) documentation, and 6) Finish. The analysis of the AC/ DC supply system for load control at the Pekalongan substation was carried out in different periods of time, namely 3 consecutive months from February 2019 to April 2019 so that the error results obtained were completely accurate. The analysis carried out can be said to be successful and the value shown by the analyzed equipment this is the actual used value because the results of measurements and calculations carried out from February 2019 to April 2019 all have an error value below 1%.